(untitled) (International Journal of Automation and Smart Technology, 2025)
This paper addresses Fault Detection and Isolation (FDI) for wind turbines based on a Proportional Multi-Integral Observer (PMIO). A wind turbine model is linearized using the Takagi-Sugeno (TS) approach based on Lyapunov stability theory and LMI condition, then the PMI observer is considered for use with the TS fuzzy model to estimate and isolate both actuator and sensor faults with the introduction of a centered noise. The kth derivatives of the actuators and sensor faults are not equal to zero but are rather bounded norms. However, based on Lyapunov stability theory and L2 performance analysis, design conditions are established through LMIs formulations. Simulation results show that our proposal outperforms some existing approaches.